The Moderating Role of Education on the Relationship Between Perceived Stereotype Threat and False Memory in Aging - Gilet, Anne-Laure; Evrard, Christelle; Galharret, Jean-Michel; Colombel, Fabienne (Frontiers in Psychology, 2021)
Studies regularly show that an age-based stereotype threat impairs older adults’ performance on memory tasks. Results regarding stereotype threat effects on false memories are less clear. Some studies suggest that education may moderate the relationship between age-related stereotype threat and episodic memory performance in older adults. The present study aimed at examining the moderating role of education on the relationship between perceived stereotype threat and false memories in older adults. With this aim, 82 adults between 60 and 70 years of age performed a Deese-Roediger-McDermott (DRM) task followed by a free recall test and completed questionnaires assessing both their perception of an age-based stereotype threat and their education level. Regression analyses showed no effect of perceived stereotype threat on the production of critical lures. However, as was expected, our results showed that in higher educated older adults, as the perception of stereotype increases, the production of critical lures increases. These results confirm the moderating role of education and highlight its key role in the relationship between age-based stereotype threat and older adults’ susceptibility to false memories.